Mitochondrial Stress Responses and “Mito-Inflammation” in Cystic Fibrosis - Patergnani, Simone; Vitto, Veronica A.M.; Pinton, Paolo; Rimessi, Alessandro (Frontiers in Pharmacology, 2020)
Cystic fibrosis (CF) is a genetic disease associated to mutations in the cystic fibrosis transmembrane conductance regulator gene, which results in the alteration of biological fluid and electrolyte homeostasis. The characteristic pathological manifestation is represented by exaggerated proinflammatory responses in lung of CF patients, driven by recurrent infections and worsen by hypersecretion of proinflammatory mediators and progressive tissue destruction. Treating inflammation remains a priority in CF. However, current anti-inflammatory treatments, including non-steroidal agents, are poorly effective and present dramatic side effects in CF patients. Different studies suggest an intimate relationship between mitochondria and CF lung disease, supporting the hypothesis that a decline in mitochondrial function endorses the development of the hyperinflammatory phenotype observed in CF lung. This allowed the implementation of a new concept: the “mito-inflammation”, a compartmentalization of inflammatory process, related to the role of mitochondria in engage and sustain the inflammatory responses, resulting a druggable target to counteract the amplification of inflammatory signals in CF Here, we will offer an overview of the contribution of mitochondria in the pathogenesis of CF lung disease, delving into mitochondrial quality control responses, which concur significantly to exacerbation of CF lung inflammatory responses. Finally, we will discuss the new therapeutic avenues that aim to target the mito-inflammation, an alternative therapeutic advantage for mitochondrial quality control that improves CF patients' inflammatory state.